Mammalian γ2 AMPK regulates intrinsic heart rate. Issue 1 (December 2017) - Yavari, Arash; Bellahcene, Mohamed; Bucchi, Annalisa; Sirenko, Syevda; Pinter, Katalin; Herring, Neil; Jung, Julia; Tarasov, Kirill; Sharpe, Emily; Wolfien, Markus; Czibik, Gabor; Steeples, Violetta; et al.
Abstract AMPK is a conserved serine/threonine kinase whose activity maintains cellular energy homeostasis. Eukaryotic AMPK exists as αβγ complexes, whose regulatory γ subunit confers energy sensor function by binding adenine nucleotides. Humans bearing activating mutations in the γ2 subunit exhibit a phenotype including unexplained slowing of heart rate (bradycardia). Here, we show that γ2 AMPK activation downregulates fundamental sinoatrial cell pacemaker mechanisms to lower heart rate, including sarcolemmal hyperpolarization-activated current (I f ) and ryanodine receptor-derived diastolic local subsarcolemmal Ca2+ release. In contrast, loss of γ2 AMPK induces a reciprocal phenotype of increased heart rate, and prevents the adaptive intrinsic bradycardia of endurance training. Our results reveal that in mammals, for which heart rate is a key determinant of cardiac energy demand, AMPK functions in an organ-specific manner to maintain cardiac energy homeostasis and determines cardiac physiological adaptation to exercise by modulating intrinsic sinoatrial cell behavior. AMPK regulates cellular energy balance using its γ subunit as an energy sensor of cellular AMP and ADP to ATP ratios. Here, the authors show that γ2 AMPK activation lowers heart rate by reducing the activity of pacemaker cells, whereas loss of γ2 AMPK increases heart rate and prevents the adaptive bradycardia of endurance training in mice.